Development of a full field-of-view spectroscopic single-molecule fluorescence instrument with improved methods for calibration - Deqi Yi; Shangyuan Deng; Chuang Tan; Jie Ma (Applied Physics Express)
We have developed a high-throughput, full field-of-view (FOV) spectroscopic single-molecule fluorescence instrument, overcoming distortion issues with gratings and prisms. Our calibration techniques ensure spectral uniformity across the whole FOV, and our two-step Gaussian fit method enables better than 2 nm precision in spectral peak determination for accurate molecule identification, making it a valuable tool for multi-color single-molecule detection and analysis.